Effects of Transportation on Stress and Fear Responses of Growing Broilers Supplemented with Prebiotic or Probiotic - Ghareeb, K.; Awad, W.A.; Nitsch, S.; Abdel-Raheem, S.; Bohm, J. (International Journal of Poultry Science, 2008)
Physiological stress response and fear levels were evaluated in broiler chickens fed control diets, chicory (1 kg/ton) and Lactobacillus sp. (1 x 108 cfu/kg) supplemented diets for 5 wk. At the end of the experiment, the birds were subjected to 80 km transport journey (90 min approximately). The fear levels of birds were measured using tonic immobility reaction (TI). The duration of TI and the susceptibility of the birds to the test were measured immediately after the birds had arrived to the laboratory and repeated after one week following their transport. Heterophil (H) counts, Lymphocyte (L) counts and Heterophil to Lymphocyte (H/L) ratios were determined immediately on arrival and at 24 h following birds transport. There was no significant differences were recorded in the fear levels of broilers supplemented with either chicory or Lactobacillus sp. compared with their control counterparts. However, in a comparison with fear levels after one week (without transport), a significant difference was observed (P=0.001) irrespective to dietary supplementation. Handling and transport on this relatively short journey was apparently equally frightening for broilers independent of dietary supplementation. H/L ratios either immediately on arrival or at 24 h following birds transport showed a significant difference between the dietary treatments. Chicory and Lactobacillus sp. supplemented groups decreased H/L ratios compared with control group which is important in reduction of stress effects on birds. In conclusion, supplementation of broiler diet with either chicory or Lactobacillus sp. can modulate the physiological stress response of transported birds and consequently enhance tolerance to stress without change in their behavioural index of fear.